Assessment of Soil Carbon Stock and Soil Quality in Different Forest Stands and Management Regimes in Terai Region of Nepal - Durga Kandel; Sachin Timilsina; Santosh Ayer; Saroj Kumar Chaudhary; Jeetendra Gautam; Rabindra Adhikari; Kishor Prasad Bhatta (Scientifica)
Assessment of soil organic carbon (SOC) stock and soil quality for informed forest management is hindered by inadequate data across different forest stand types and management regimes. Therefore, this study was conducted to assess SOC stock and soil quality in two forest stand types, i.e., Shorea robusta (Sal) forest and Terai mixed hardwood (TMH) forest, and selected forest management regimes (leasehold forest, community forest, government-managed forest, and forest area under protected area) in Terai region of Nepal. Stratified random sampling method was adopted for soil sample collection across terai region following Forest Resource Assessment, Nepal. Altogether, 62 composite soil samples from 30 cm depth were taken from the entire Terai region which included these two forest stand types and four management regimes. Different physical (soil texture and bulk density) and chemical (pH, SOC (%), total nitrogen, available phosphorus, and available potassium) properties were analyzed to calculate SOC stock and soil quality. Our result found no significant differences in SOC stock among two forest stand types (p>0.05). Unexpectedly, leasehold forest had significantly (p<0.05) higher SOC stock than other forest management regimes. In terms of soil quality, among two forest stand types, Sal forest (0.50) was found to be superior compared with TMH forest (0.46). Similarly, community forest had superior soil quality (0.50) than government-managed forest (0.47), protected area (0.47), and leasehold forest (0.45). A longitudinal study approach is recommended to observe changes in soil properties over time due to climate change and human activities, offering valuable insights into their dynamics.